Brush Road house fireplace - Richard L. Allman:::Creator::::::::::::
Five images and views of Steinbeck's Brush Road house fireplace. Steinbeck designed the copper hood of fireplace. John and Carol Steinbeck lived here from 1938-1940. Photo number 0-785 included on this sheet. RESTRICTED USE